Electronic health record in the general health system of Cyprus: Evaluation of users' satisfaction levels - Rompolas, Periklis; Masouras, Panicos; Avgousti, Sotiris; Charalambous, Andreas (Health & Research Journal, 2025)
Background: The Electronic Health Record (EHR) is a technological tool for eHealth that is a strategic priority internationally in health systems. Since 2019, Cyprus has universally applied the EHR in the General Health System (GHS). This study aimed to assess the levels of satisfaction among EHR users in the GHS of Cyprus. Material and Method: During the period from October to December 2022 the first cross-sectional study was carried out to evaluate users’ satisfaction levels of EHR through an online self-reporting questionnaire. The questionnaire was distributed electronically using the convenience sampling method and included questions about demographic characteristics and satisfaction. A total of 429 physicians participated in the study. Results: According to the results, moderate users’ satisfaction levels of the EHR were found. There was also a statistically significant relationship between satisfaction with the EHR and factors such as age, years of professional practice, familiarity with the use of ICT and familiarity with EHR, education/training provision prior to the use of EHR and support during the daily practice. The study’s limitations include the absence of a comparative sample of other healthcare professionals, such as nurses, and the reliance on international data for comparison, owing to the lack of relevant scientific evidence from Cyprus. Conclusions: To fulfill Cyprus’ strategic goals for eHealth, within the European framework, health policy makers should implement EHR improvements in the context of GHS. Users’ training, support and equal access for all health professionals are essential. Finally, new studies must be conducted in the rapidly changing field, so that new developments can be identified and results compared so that enhancements, new services and functionalities are implemented for the benefit of the citizens.